Pathology of University in Educating a Responsible Citizen and Solutions to Modify it - Alireza Tanhayee (مطالعات منابع انسانی, 2022)
Background & Purpose: In today's society, one of the main duties of the university should be to train responsible citizens who not only feel self-worth but also consider themselves members of society. In addition, these citizens should not only face and solve problematic situations but also be able to take on various responsibilities in society and have high social participation. Accordingly, the purpose of this study is to examine the role of the university in educating a responsible citizen and to provide effective solutions.Methodology: This research is applied in terms of purpose and has been done using a qualitative approach and content analysis. Participants of this study are university administrators, professors, experts, and specialists (employees of universities, related institutions and organizations) with a doctoral degree and at least 15 years of service. For sampling, the snowball targeted method has been used to the extent of theoretical saturation.Findings: The analysis of the information collected in the interviews using open and axial coding indicates that the most important fundamental harms in reducing the effectiveness of the administrators of the universities of the Islamic Republic of Iran in educating responsible citizens include: the uncontrolled spread of quantitativeism in the development of universities and the weakness of quality, the weak relationship among academia, society, and industry, and the wrong system of promoting professors. Besides, the most important and effective ways to achieve this goal include: rethinking institutional values of university, establishing educational sites in the city with the help of other social institutions (municipality), reviewing the functions of higher education by specialists and experts in educational sciences.Conclusion: Applying strategies to improve the role of the university in educating responsible citizens can provide the ground for sustainable development in country by producing and promoting sustainable order and strengthening, deepening, and developing the values ​​of democracy in society.